A single Streptomyces symbiont makes multiple antifungals to support the fungus farming ant Acromyrmex octospinosus. - Ryan F Seipke; Jörg Barke; Charles Brearley; Lionel Hill; Douglas W Yu; Rebecca J M Goss; Matthew I Hutchings (PLoS ONE)
Attine ants are dependent on a cultivated fungus for food and use antibiotics produced by symbiotic Actinobacteria as weedkillers in their fungus gardens. Actinobacterial species belonging to the genera Pseudonocardia, Streptomyces and Amycolatopsis have been isolated from attine ant nests and shown to confer protection against a range of microfungal weeds. In previous work on the higher attine Acromyrmex octospinosus we isolated a Streptomyces strain that produces candicidin, consistent with another report that attine ants use Streptomyces-produced candicidin in their fungiculture. Here we report the genome analysis of this Streptomyces strain and identify multiple antibiotic biosynthetic pathways. We demonstrate, using gene disruptions and mass spectrometry, that this single strain has the capacity to make candicidin and multiple antimycin compounds. Although antimycins have been known for >60 years we report the sequence of the biosynthetic gene cluster for the first time. Crucially, disrupting the candicidin and antimycin gene clusters in the same strain had no effect on bioactivity against a co-evolved nest pathogen called Escovopsis that has been identified in ∼30% of attine ant nests. Since the Streptomyces strain has strong bioactivity against Escovopsis we conclude that it must make additional antifungal(s) to inhibit Escovopsis. However, candicidin and antimycins likely offer protection against other microfungal weeds that infect the attine fungal gardens. Thus, we propose that the selection of this biosynthetically prolific strain from the natural environment provides A. octospinosus with broad spectrum activity against Escovopsis and other microfungal weeds.